The impact of financial inclusion on the efficiency of financial performance - Mohammed, Asst.Prof.DrAyad Taher Mohammed; Kazem, L.Dr.Fatima Faisal Kazem (Sulaimani Journal for Humanities, 2026)
This research aims to study the impact of financial inclusion on the financial performance efficiency of the banking sector in Iraq, for the period from 2015 to 2024. This study uses the number of electronic payment transactions recorded to measure the financial inclusion variable on the financial performance efficiency of banks. Three financial indicators address aspects of financial performance evaluation: profitability, liquidity, and solvency, measured by return on assets, capital adequacy, and the ratio of non-performing loans to total loans. Simple linear regression was used using the SPSS V.26 statistical package to compare the calculated results and test the hypotheses. The importance of the research emerges from its study of the financial inclusion variable as a cornerstone of sustainable financial development, and its impact on three aspects that are being closely monitored and studied by bank owners and clients. The results showed a significant positive effect of financial inclusion on profitability, while there was no significant effect of financial inclusion on either capital adequacy or solvency in banks.
Keywords: Financial inclusion; profitability; solvency; liquidity; CAR; ROA; NPL